IMS 552: Information Systems Management. Group Assignment: Information System in Kolej Matrikulasi Kok Lanas / Mohamad Azran Aziz, Muhammad Faiz Afiq Mohd Yusof and Mohd Syahir Rahim - Aziz, Mohamad Azran; Mohd Yusof, Muhammad Faiz Afiq; Rahim, Mohd Syahir (2015)
In this assignment, we decided with our group members to choose Kelantan Matriculation College as one of a public institution of higher learning in Kok Lanas, Kota Bharu, Kelantan to make a study about the uses of the system at their administration. On 29 November 2015, we have made a visit to survey and consulted and interviewed one information technology officer, Mohd Syafizal Bin Jusoh who has incharge the unit data and information at Kelantan Matriculation College. We chose this place because it is one of the new higher education institutions in Kelantan was completed in 2014 and started operating in May 2014 and we are interested to make a research on the uses of the information system in there and how it is operated. So, a lot of information we get and kept referred as a study and it also very interesting things and a lot of things we've learned about the uses of the system in Kelantan Matriculation College, which is e-matris system, it also have used these systems as an alternative method in their facilities and in the management of information, records, managing external relations and others. E-matris system which is a facility available to serve and manage the administrative in that college and it also the only one as a system in a centralized system and based on the data and information unit. The administration of Kelantan Matriculation College also preferred the paperless method than manual use for example paper, letter, memo and others. So, the e-matris system being the platform for administration department and it is also specially prepared for lecturer, staff and student in of Kelantan Matriculation College only.